Production of Fumonisins by Fusarium moniliforme and Fusarium proliferatum Isolates Associated with Equine Leukoencephalomalacia and a Pulmonary Edema Syndrome in Swine - Ross, P. F.; Nelson, P. E.; Richard, J. L.; Osweiler, G. D.; Rice, L. G.; Plattner, R. D.; Wilson, T. M. (Applied and Environmental Microbiology, 1990)
During the 1989 corn harvest season, the National Veterinary Services Laboratories received numerous reports of outbreaks of equine leukoencephalomalacia (ELEM) and a porcine pulmonary edema syndrome (PPE). The PPE outbreaks were generally confined to the central portion of the United States, while ELEM cases in several states, ranging from Arizona to Maryland, were reported. In almost all cases, feed containing corn and/or corn screenings from the 1989 harvest was implicated as the causative factor. Because ELEM is known to be caused by fumonisin B, (FB,) (4), a mycotoxin produced by Fusarium moniliforme, and because a PPE-like syndrome caused by feeding F. moniliforme culture material (CM) to swine has been reported (3), feed samples were collected for mycological evaluation and chemical analyses. Nine feed samples were obtained from farms in southeastern Iowa: two were associated with an ELEM case (284A and 284B), five were associated with PPE cases (943A, 567, 615, 317A, and 378B), and two were not associated with animal health problems (943B and 317B).
Keywords: Fumonisins; Fusarium moniliforme; Fusarium proliferatum; Equine Leukoencephalomalacia; Pulmonary Edema Syndrome